2023
DOI: 10.1002/hsr2.1147
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of congenital heart disease in Nepal from 2002–2022: A systematic review and meta‐analysis

Abstract: Background: Congenital heart diseases are recognized as public health concerns worldwide and Nepal is no exception. This study aims to study congenital heart disease in Nepal on grounds of burden, commonest type, common presentations, and associated noncardiac anomalies so that its spectrum can be known for prompt diagnosis and adoption of screening protocols.Methods: Relevant articles were searched in electronic databases using appropriate search terms and Boolean operators. Data were extracted in Excel and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The prevalence of a past study conducted in a similar setting showed the prevalence of congenital heart disease in Nepal was 0.7%. 6 Indian studies had reported a wide variation in prevalence of CHD from 2.25 to 26 per 1000 live birth. 5 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of a past study conducted in a similar setting showed the prevalence of congenital heart disease in Nepal was 0.7%. 6 Indian studies had reported a wide variation in prevalence of CHD from 2.25 to 26 per 1000 live birth. 5 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Among 249 patients undergoing echocardiography, 70 cases of congenital heart disease was observed with proportion of 28%.The prevalence of a past study conducted in a similar setting showed the prevalence of congenital heart disease in Nepal was 0.7%. 6 Indian studies had reported a wide variation in prevalence of CHD from 2.25 to 26 per 1000 live birth. 5,7,8 In our study, there was a male predominance of 65.50%, a trend observed in similar studies.…”
Section: Discussionmentioning
confidence: 99%